2014
DOI: 10.1002/fld.3888
|View full text |Cite
|
Sign up to set email alerts
|

Efficient p‐multigrid discontinuous Galerkin solver for complex viscous flows on stretched grids

Abstract: SUMMARYDiscontinuous Galerkin methods are very well suited for the construction of very high‐order approximations of the Euler and Navier–Stokes equations on unstructured and possibly nonconforming grids but are rather demanding in terms of computational resources. In order to improve their computational efficiency, a p‐multigrid solution strategy is here considered for the solution of the Navier–Stokes equations. In particular, a line smoother will be used to alleviate the effect of stretched grids on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…As confirmed in cases 2 and 3, the linear solvers are more robust than the nonlinear one. However, through all test cases, it has been found that achieving a robust convergence in some sense contradicts achieving an efficient convergence (see e.g., Figures 4,8,and 9). And for all solvers in this work, we can claim that it is the CFL scheduling strategies that play a significant role in the balance between efficiency and robustness of high-order RANS computation.…”
Section: Steady Flow Simulationsmentioning
confidence: 64%
See 1 more Smart Citation
“…As confirmed in cases 2 and 3, the linear solvers are more robust than the nonlinear one. However, through all test cases, it has been found that achieving a robust convergence in some sense contradicts achieving an efficient convergence (see e.g., Figures 4,8,and 9). And for all solvers in this work, we can claim that it is the CFL scheduling strategies that play a significant role in the balance between efficiency and robustness of high-order RANS computation.…”
Section: Steady Flow Simulationsmentioning
confidence: 64%
“…And similar to classical geometric multigrid methods, p ‐multigrid method is a scheme in which the system of equations is solved by recursively iterating on solution approximations of different polynomial orders. The idea of p ‐multigrid was originally proposed by Ronquist and Patera and then was pursued for the Euler and NS equations for high‐order schemes by various authors . However, p ‐multigrid algorithms have been rarely extended to high‐order DG discretizations of the RANS equations .…”
Section: Introductionmentioning
confidence: 99%
“…Work is underway to implement a dual time stepping technique to solve the nonlinear system arising at each MEBDF stage, based on a p ‐multigrid strategy , and to compare the performance of different high‐order time integration schemes (MEBDF, TIAS , ESDIRK, and Rosenbrock methods). Preliminary results for compressible inviscid and viscous test cases show that MEBDF4 scheme performs better than ESDIRK4 and TIAS4, but it is outperformed by TIAS6 and Rosenbrock (with order greater than three) schemes.…”
Section: Discussionmentioning
confidence: 99%
“…The objective functional, formally obtained by increasing the degree of the discretization from k to k +1, is approximated to avoid the computational expense of solving a higher degree DG discretization of the nonlinear system of equations, see also Hartmann et al and Hartmann and Houston . The approximation relies on the Taylor series expansion of J k +1 ( W k +1 ) about the L 2 ‐projection boldwkk+1 of the solution w k on V k +1 Jk+1()Wk+1Jk+1()Wkk+1+()Jk+1Wk+1boldWkk+1()Wk+1Wkk+1. Similarly, the vector of the residuals is expanded about boldWkk+1 Rk+1()Wk+1Rk+1()Wkk+1+[]Rk+1Wk+1boldWkk+1()Wk+1Wkk+1. In practice, when orthogonal and hierarchical modal bases are used, the degrees of freedom of the projected solution are the same of the low‐order one with null higher‐order modes …”
Section: Adjoint‐based Error Estimationmentioning
confidence: 99%
“…In practice, when orthogonal and hierarchical modal bases are used, the degrees of freedom of the projected solution are the same of the low-order one with null higher-order modes. 36 Since the unknown W k+1 is the solution of the higher-order discretization of the nonlinear problem, we have R k+1 (W k+1 ) = 0. Thus, by rearranging Equation 14, we obtain the following error representation…”
Section: Formulation Of the Adjoint Problemmentioning
confidence: 99%